NUKUS SHAHRIDA MUSICHA STREPTOPELIA SENEGALENSIS NING BIOEKOLOGIYASI BO‘YICHA MATERIALLAR - Ametova N.I., Ametova N.I.; Jumanov M.A., Jumanov M.A.; Ametov Y.I., Ametov Y.I.; Babanov R.S., Babanov R.S.; Alimova U.Z. , Alimova U.Z. (Actual problems and prospects of the study of the fauna, 2024)
The article describes the collected materials on the bioecology of the Laughing Dove in the city of Nukus in 2021-2024. The authors studied the distribution, nesting, reproduction and nutrition of the Laughing Dove.